Religious and spiritual coping in people living with HIV/Aids - Clarissa Mourão Pinho; Bruno Felipe Remigio Dâmaso; Eduardo Tavares Gomes; Maria de Fátima Cordeiro Trajano; Maria Sandra Andrade; Marília Perrelli Valença
ABSTRACT Objective: evaluate the religiosity and the religious/spiritual coping of people living with HIV/Aids. Method: descriptive, cross-sectional study with quantitative approach, conducted in a reference HIV/Aids outpatient clinic in a university hospital of Recife-PE, Brazil, from June to November 2015. At total of 52 people living with HIV/Aids (PLWHA) participated in the research, which employed own questionnaire, the Duke University Religion Index (DUREL), and the Religious/Spiritual Coping Scale (RCOPE). Results: the sample presented high indices of organizational religiosity (4.23±1.66), non-organizational religiosity (4.63±1.50), and intrinsic religiosity (13.13±2.84). Positive RCOPE was used in high mean scores (3.66±0.88), and negative RCOPE had low use (2.12 ± 0.74). In total, use of RCOPE was high (3.77±0.74), having predominated the positive RCOPE (NegRCOPE/PosRCOPE ratio=0.65±0.46). Conclusion: it is evident the importance of encouraging religious activity and RCOPE strategies, seen in the past as inappropriate interventions in clinical practice.